Establishing credibility: Evolving perceptions of the European Central Bank - Linda S. Goldberg; Michael W. Klein (Federal Reserve Bank of New York, 2005)
The perceptions of a central bank's inflation aversion may reflect institutional structure or, more dynamically, the history of its policy decisions. In this paper, we present a novel empirical framework that uses high-frequency data to test for persistent variation in market perceptions of central bank inflation aversion. The first years of the European Central Bank (ECB) provide a natural experiment for this model. Tests of the effect of news announcements on the slope of yield curves in the euro area and on the euro-dollar exchange rate suggest that the market's perception of the policy stance of the ECB evolved significantly during the first six years of the Bank's operation, with a belief in its inflation aversion increasing in the wake of its monetary tightening. In contrast, tests based on the response of the slope of the U.S. yield curve to news offer no comparable evidence of any change in market perceptions of the inflation aversion of the Federal Reserve.
Keywords: F3; E5; E6; 330; central banking; European Central Bank; Federal Reserve; inflation; exchange rate; monetary policy; credibility; yield curve; Zentralbank; Inflation; Inflationsbekämpfung; Geldpolitik; Wechselkurs; Glaubwürdigkeit; EU-Staaten